ANALYSIS OF COMPANY VALUE AT PT BANK RAKYAT INDONESIA (PERSERO) Tbk PERIOD 2018-2022 - Rismawati; Anwar, Andi Mustika Amin, Romansyah Sahabuddin, M Ikhwan Maulana Haeruddin (Jurnal Ekonomi dan Bisnis, 2024)
Based on the results of research that researchers have conducted, it can be concluded that the shares of PT. Bank Rakyat Indonesia (Persero)., Tbk, which is one of the largest government-owned banks in Indonesia and the oldest in Indonesia. Over the years, with various banking facilities, PT. Bank Rakyat Indonesia (Persero) is trusted and reliable for the Indonesian people, making it one of the leaders in the banking world in providing financial services to underprivileged segments of society, including through microfinance programs and small business financing with programs designed to help the community. in overcoming current economic problems.